Determination of environmental, social and corporate governance indicators: framework in the measurement of sustainable performance - Kocmanová, Alena; Šimberová, Iveta (Journal of Business Economics and Management, 2014)
The article is concerned with determination of environmental, social and corporate governance (ESG) indicators of performance. The objective of carried-out empirical research is to determine ESG indicators as a key framework of the measurement of sustainable performance of a company in its Sustainable Reporting. On the basis of conducted empirical research, applying factor analysis, the environmental, social and corporate governance indicators for companies active in the processing industries CZ-NACE have been specified. The indicators were selected in a series of successive phases by a multi-factor analysis. The results of factor analysis indicated that the factors fall into three measurement categories: environmental (Investments, Emissions, Source Consumption, Waste), social (Society, Human Rights, Labour Practices and Decent Work, Product Responsibility), and corporate governance (Monitoring and Reporting, Corporate Governance Effectiveness, Corporate Governance Structure, Compliance). This article contributes to the effort to solve measurement of performance of the corporate sustainability and proposal to conceptual framework of ESG indicators of performance for the Sustainability Reporting of Czech companies operating in the processing industry.